Yoga Pandita Texts And Contexts In Griyas Buleleng Regency - Luh Asli (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2020)
Yoga is increasingly more favorite  among a large part  of  communities of the world crossing religious and cultural backgrounds  It has become a lifestyle because of the benefits that the people who practice it.  It is one of the spiritual assets and wisdoms of Hinduism offered to the world, not only in India, but also in Bali, both in terms of text and context.  A number of texts in Bali contain theories and practices of what is  called Yoga Pandita. The sources of this type  are found and actualized  within griyas.  Actually,  people havee taught Yoga Pandita  since the emergence of  griyas in Bali. Griya is a place in Bali where traditional Hinduism education takes place. A number ot texts such as   Silakrama, Wrspati Tatwa, Sivasasana, Ganapati Tatwa  are used as guides in actualizing yoga within the griyas. Most of the practices of Yoga Pandita in the griya areas especially in those in Buleleng regency tend  to practice samyama  or Raja Yoga and only a small part practices  Hatha Yoga.  This is caused by the factors such as  age, degradation in physical ability , however in terms of mental ability and mind control and spirituality the people who practice  yoga increasily more stable. This is a ladder in the esoteric world and is relevant in making progress of  Astanggayoga  in  Patanjali Yogasutra.